2019
DOI: 10.1080/15476286.2019.1581597
|View full text |Cite
|
Sign up to set email alerts
|

Time resolved gene expression analysis during tamoxifen adaption of MCF-7 cells identifies long non-coding RNAs with prognostic impact

Abstract: Acquired tamoxifen resistance is a persistent problem for the treatment of estrogen receptor positive, premenopausal breast cancer patients and predictive biomarkers are still elusive. We here analyzed gene expression changes in a cellular model to identify early and late changes upon tamoxifen exposure and thereby novel prognostic biomarkers. Estrogen receptor positive MCF-7 cells were incubated with 4OHtamoxifen (10 nM) and gene expression analyzed by array hybridization during 12 weeks. Array results were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(37 citation statements)
references
References 69 publications
1
35
1
Order By: Relevance
“…[6][7][8][10][11][12][13] Recent studies have revealed that lncRNAs played vital roles in the development of cancers. 21,22 Further, germline mutations can also predict tumor recurrence in breast cancer patients. 38 In the present study, we used ceRNA to detect and validate potential prognostic lncRNAs in the luminal BC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][10][11][12][13] Recent studies have revealed that lncRNAs played vital roles in the development of cancers. 21,22 Further, germline mutations can also predict tumor recurrence in breast cancer patients. 38 In the present study, we used ceRNA to detect and validate potential prognostic lncRNAs in the luminal BC.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, prognostic roles and relationship with tamoxifen resistance were also mentioned. 13,22 Recently, competitive endogenous RNA (ceRNA), as a whole view of transcription, has gradually become a useful tool for identifying prognostic lncRNAs. The ceRNA hypothesis suggests that lncRNAs can competitively bind to miRNAs, thereby preventing their binding to mRNA, and consequently regulating mRNA expression.…”
Section: Introductionmentioning
confidence: 99%
“…MCF-7 cells and a tamoxifen adapted MCF-7 cell line [24,25] were used for these studies. Cells were seeded onto glass slides (Sarstedt), fixed using ice cold methanol followed by acetone (− 20 °C) for 5 min each.…”
Section: Indirect Immunofluorescencementioning
confidence: 99%
“…In addition to earlier studies on anti-estrogen resistance and the effect of cancer-associated fibroblasts, we initially investigated the BCL3 expression in our model for acquired tamoxifen resistance. In this model, the luminal A cell line MCF-7 was adapted to 4OH-tamoxifen for at least 12 weeks [23,24]. Here, we were particularly interested whether BCL3 localization and abundance has changed.…”
Section: Analysis Of Bcl3 Expression In Tamoxifen Adapted Cell Lines ...mentioning
confidence: 99%
“…Emerging evidence has indicated that lncRNAs Blnc1 ( 157 ), MALAT1 ( 158 162 ), Nrf2-lncRNA ( 163 ), AK094457 ( 164 ), Linc01213 ( 165 ), lncRNA74.1 ( 166 ), ODRUL ( 167 ), SNHG14 ( 168 ), UCA1 ( 126 ), LUCAT1 ( 169 ), TUG1 ( 170 172 ), Loc344887 ( 173 ), H19 ( 174 ), Mhrt ( 175 ), MIAT ( 176 ), MRAK052686 ( 177 ), AATBC ( 178 ), HOTAIR ( 179 ), NRAL ( 129 ), H19 ( 114 ), Sox2OT ( 180 ), MT1DP ( 125 ), MEG3 ( 127 , 128 , 181 ) and KRAL ( 117 ) may activate Nrf2 signaling by targeting Nrf2-related genes. Furthermore, circRNA-4099 may activate Nrf2 signaling by targeting miR-706, which augments H 2 O 2 -induced cell damage in the L0 2 cells ( 182 ).…”
Section: Role Of Ncrnas In Ferroptosis and Cancer Developmentmentioning
confidence: 99%